2013
DOI: 10.1111/iju.12090
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐6 levels in female rats with protamine sulfate‐induced chronic cystitis treated with hyaluronic acid

Abstract: Abbreviations & Acronyms BC = bladder capacity BP = base pressure BPS = bladder pain syndrome CMG = cystometrogram ELISA = enzyme-linked immunosorbent assay GAG = glycosaminoglycan GAPDH = glyceraldehydes-3-phosphate dehydrogenase HA = hyaluronic acid IC = interstitial cystitis ICI = intercontraction intervals IL-6 = interleukin-6 mRNA = messenger ribonucleic acid NS = normal saline PP = peak pressure PS = protamine sulfate RNA = ribonucleic acid RT-PCR = reverse transcription polymerase chain reaction RV = re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 29 publications
4
28
0
Order By: Relevance
“…In the present study, levels of IL‐1β and TNF‐α, which are usually increased in acute inflammation, did not change; whereas the level of IL‐6 increased along with the severity of inflammation. The present results were similar to those of some experimental or clinical trials in BPS . IL‐6, as an important factor in acute and chronic inflammation, has a strong relationship with bladder fibrosis and detrusor overactivity, and can be used as an objective indicator for the inflammatory process of the BPS model and an effective assessment for therapeutic impact …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the present study, levels of IL‐1β and TNF‐α, which are usually increased in acute inflammation, did not change; whereas the level of IL‐6 increased along with the severity of inflammation. The present results were similar to those of some experimental or clinical trials in BPS . IL‐6, as an important factor in acute and chronic inflammation, has a strong relationship with bladder fibrosis and detrusor overactivity, and can be used as an objective indicator for the inflammatory process of the BPS model and an effective assessment for therapeutic impact …”
Section: Discussionsupporting
confidence: 89%
“…In the HAase‐treated groups, a PE‐50 catheter (Clay Adams, Parsippany, NJ, USA) was inserted into the bladder through the urethra to empty the bladder, and then 0.5 mL HAase (1 mg/mL or 4 mg/mL) was infused intravesically for 30 min. In the HA‐treated group, 6 h after HAase (1 mg/mL) instillation, the rats were intravesically instilled with 0.5 mL of HA (0.8 mg/mL, Bioniche, Belleville, Ontario, Canada) at each time . In the control group, 0.5 mL saline was infused following the same procedure.…”
Section: Methodsmentioning
confidence: 99%
“…Lv et al . recently reported that in a protamine sulphate intermittent cystitis model, IL‐6 bladder expression has a positive correlation with histological inflammation grade, and a negative correlation with the bladder intercontraction interval measured at cystometry . Both correlations were influenced by intravesical administrations of HA: reduction of IL‐6 expression with lower inflammatory grade, longer voiding frequency and higher bladder capacity.…”
Section: Methodsmentioning
confidence: 93%
“…Finally, the GAG effect on the inflammatory process was also investigated though urinary markers . Lv et al .…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, Lv et al . investigated the correlation between interleukin (IL)‐6 levels and the inflammatory degree, as well as the voiding frequency in protamine sulfate‐induced chronic cystitis rats with or without treatment of hyaluronic acid . They concluded that tissue levels of IL‐6 might be an effective assessment of the therapeutic impact of interstitial cystitis/bladder pain syndrome (IC/PBS).…”
mentioning
confidence: 99%